Recording the Door-To-ECG Time for Patients Presenting with Acute Chest Pain to a Cardiac Emergency Unit: A Clinical Audit and Quality Improvement Project - Sami, Ashar; Maqsood, Sarah; Iqbal, Usman; Safdar, Haadia; Khalil, Hafsa; Yasir, Saad Bin; Khan, Aleena; Shafique, Hafiz Muhammad; Javaid, Rehana; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To measure the door-to-ECG time of patients presenting with chest pain at a Cardiac Emergency Unit.Study Design: Descriptive Cross-Sectional.Place and Duration of Study: Armed Force Institute of Cardiology/National Institute of Heart Disease, Emergency Department (ER) from Feb2022 to Apr 2022.Methodology: A total of 170 patients presenting to the ER with chest pain were reported. Their demographics were entered alongside the nature (cardiac/non-cardiac) and duration of their chest pain after which the time the first ECG strip was drawn till the time it was interpreted by a doctor (Door-To-ECG time) was recorded on a questionnaire. The patients were categorized in 4 different groups based on their ECG findings and were followed till their clinical decisions (PCI/Admission/Discharge/Referral) within the ER were made.Results: Out of 170 patients, 101(59.4%) had a door-to-ECG time within 10 minutes. Amongst these 101 patients, 23(22.7%)patients were diagnosed with STEMI and shifted for PCI, 15(14.8%) had NSTEMI and were admitted for management,41(40.6%) had cardiac chest pain without ECG changes and were admitted for workup while 22(21.8%) had non-cardiac chest pain and were discharged with out-patient follow-up or referred elsewhere. Non-availability of a bed in the emergency department accounted for the majority (49.3%) of the patients whose door-to-ECG time was more than 10 minutes while a higher ratio of patients that needed to be attended by doctors was identified as the second most common cause of delay(31.9%).Conclusions: Our findings suggest that the door-to-ECG time recorded for patients at our setup was almost 10 minutes....